1993
DOI: 10.1002/hlca.19930760208
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and Structural Properties of Non‐Steroidal Anti‐inflammatory Oxicams

Abstract: Using the five therapeutic oxicams 1-5, we showed that isosteric replacements result in remarkable changes in the physicochemical and structural properties of congeners. Thus, the acidity of the phenolic OH group is relatively higher in the oxicams containing a pyridinyl moiety, i.e. in piroxicam (l), tenoxicam (2), and lornoxicam (3), due to their zwitterionic nature. This consequently influences their lipophilicity profile at different ionization states. Furthermore, partitioning behaviour in octan-1 -ol/H,O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 27 publications
4
92
0
3
Order By: Relevance
“…2. The correlation between the experimental capacity factors of the compounds studied over the whole experimental pH range was good, as shown in In this study, the pK a values of the enolic OH group of the oxicams and carboxylic group of naproxen were determined by using LC methodology [38]. The simultaneous determination of pK a values together with the k HA and k A from k/pH data was carried out by using the software NLREG 4.0 [39].…”
Section: Resultsmentioning
confidence: 98%
“…2. The correlation between the experimental capacity factors of the compounds studied over the whole experimental pH range was good, as shown in In this study, the pK a values of the enolic OH group of the oxicams and carboxylic group of naproxen were determined by using LC methodology [38]. The simultaneous determination of pK a values together with the k HA and k A from k/pH data was carried out by using the software NLREG 4.0 [39].…”
Section: Resultsmentioning
confidence: 98%
“…It is known that pir oxicam can exist in the zwitterionic form in aqueous solutions 41,45,48 or at acidic pH values as a result of the protonation of the pyridine fragment of the molecule. 44,47,49 Earlier, the transforma tion of piroxicam  form to its  form 21 and the zwitteri on 21,23 was also observed during the preparation of mech anocomposites of piroxicam with biopolymers (chitosan and cellulose).…”
Section: Ag-so 3 H = Agsmentioning
confidence: 99%
“…Several studies related with the acid-base behavior of Piroxicam have been reported in the literature [32][33][34][35][36][37]. Being a diprotic amphoteric drug with pKa values differing by less than 4 units, the deprotonation-protonation of one group affects the other depending on the pH values of the media.…”
Section: Acid-base Behavior Of Piroxicammentioning
confidence: 99%